PERBANDINGAN PERSAMAAN KOEFISIEN PERPINDAHAN KALOR KESELURUHAN UNTUK PERANCANGAN PENUKAR KALOR - Yuli Setyo Indartono; Ari Darmawan Pasek (Mesin, 1996)
This paper concerns with comparison of various heat transfer equations which can be used in the design of a shell and tube heat exchanger for combustion gas and air. A computer programme which also includes the thermodynamics properties of the gas and air was made for that purpose. Characteristics of the heat exchangers are then compared with the existing industrial heatexchanger. It was found that the overall heat transfer coefï¬cient equation proposed by Babcock & Wilcock gives the best results .